PEMESINAN DAN PENGALAMAN PRAKTIK KERJA INDUSTRI DENGAN KESIAPAN KERJA DI INDUSTRI - Choirul Mufti Nurhidayat; Subagyo Subagyo (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this study is to find out the relationship between machining learning achievement and industry work experience together with work readiness in the industry. This type of research is ex-post facto. Methods of data collection used questionnaires and documentation. Data analysis techniques using inferential statistical analysis, test the first and second hypotheses using the partial correlation test and the third hypothesis test using multiple regression which is preceded by tests of normality, linearity and independence. The results of the study show that: (1) there is a positive and significant relationship between machining learning achievement and industrial work practice experience together with work readiness in the industry with a calculated R value = 0.344 with the contribution 11.8%. (2) There is a positive and significant relationship between machining learning achievement and work readiness in industry with r count = 0.244 with a significant level of 0.014 <0.05. (3) There is a positive and significant relationship of industrial work practice experience with work readiness in the industry with a value of r count = 0.242 with a significant level of 0.015 <0.05. The machining learning achievement gave contribution 5.8% and industrial work practice experience gave contribution 6.0% toward work readiness in the industry.